Reimagining Divine Presence: Interpretation Of Matthew 28:20b And The Song “O Mawu Rendingane” As The Voice Of Sangihe Community - Adilang, Ryanto; Kalintabu, Heliyanti; Udang, Frety Cassia; Tombokan, Tifany Fergie (Gereja Alkitab Anugerah Kadoudan, 2025)
Living life on earth as a human being is certainly not free from various challenges and problems. In our fragility, humans will always depend on God to prevent collapse when faced with life's challenges. For this reason, God's presence is crucial in human life and faith. Matthew 28:20B presents Jesus' narrative about His promise of presence to his disciples. Therefore, this study aims to highlight this promise of presence in a dialogue with the voices of the local community through the song